Enhancing Attack Detection Time in Industrial Systems Using Machine Learning Techniques - Mussaveer Tungal (International Journal of Intelligent Systems and Applications in Engineering, 2023)
Sophisticated cyber-harsh are aimed at rapid industrial systems, which asks for sharp and accurate intrusion detection devices. Delayed attack detection period can cause major operational disturbances and financial losses, so traditional security methods typically struggle with them. This paper examines the methods of machine learning to increase the time to detect attacks in industrial systems to resolve the issue. “The main goal is to improve the discrepancy-based infiltration by suggesting the maximum posterior dicotomus dicotomous discriminatory jaccardized rocchio loud (MPDQDJREB)” classification structure. This innovative approach reduces the processing load when detecting discrepancy by combining probable classification with geometry and equality-based learning. The decision limit refinement is done using the maximum backward-devious quadratic analysis (mpdqd) by the suggested model, the similarity-propelled discrepancy classification is done using jaccardized rocchio emphasis boost (JREB), and accurateness is increased using an adaptive learning technique. Using the benchmark industrial infiltration dataset, the evaluation of the approach was shown to detect a 16% sharp attack than the traditional machine learning model. Classification with processing speeds the ability of framework to balance the classification accuracy, so guarantee the reaction to real -time danger, responsible for promoting this efficiency. By greatly reduced the delay in detecting discrepancies, the results suggest how mpdqdjreb can improve the cyber security flexibility of industrial systems. Research has found that hybrid classification methods in industrial cyber security systems can be added to maximize maximum accuracy and efficiency. Future studies can emphasize modifying the model for dynamic industrial environments' real-time deployment, hence strengthening the proactive protection mechanisms against changing cyber threats.